Effect of Cannabis seeds on Some biomedical parameters in male rats - Hassan, Karwan Anwar (Kurdistan Journal of Applied Research, 2022)
Cannabis, sometimes known as hemp, is a plant that originated in Central Asia. Cannabis seeds nutritional profile is astounding. Cannabis seed, most digestible, balanced, natural, and complete supply of protein, amino acids, and necessary fats found anyplace in nature when it is in its pristine organic natural condition. Cannabis seeds can be used in a variety of medical fields. Each 100 gm of the seeds used in the study contains 26, 37 and 20 gm of protein, fat and carbohydrate respectively. The present study used two groups of male rats (control and treatment groups). Rats were 11 weeks of average age. 10 mg/kg of body weight of powdered cannabis seeds were administrated orally to treatment group daily for 15 days. Alkaline Phosphatase, glutamic oxaloacetic transaminase and glutamic pyruvic transaminase (ALP, GPT, and GOT), creatinine and uric acid was done for estimating the effect of cannabis seeds on renal and liver function. Enzymes Alkaline phosphatase, glutamic oxaloacetic transaminase and glutamic pyruvic transaminase (ALP, GPT, and GOT) as well as creatinine, uric acid and very low-density lipoprotein (VLDL) were not significantly (p<0.05) different in both groups. Level of Cholesterol, triglyceride and c-reactive protein were significantly (p<0.05) reduced. Serum total protein, albumin and globulin were significantly (p<0.05) elevated in treatment group comparing to control group. The aim of this study is to examine physiological impact of cannabis whole seeds. Identifying the relationship(s) between liver and renal functions and cannabis seeds, as well as the anti-inflammatory effect of cannabis seeds and possible of using cannabis seeds as herbal medicine for health care in male rats.